Analisis Regresi Linier Berganda dengan Faktor-Faktor yang Mempengaruhi Tingkat Kemiskinan di Provinsi Sumatera Utara Tahun 2021-2023 (IJM: Journal of Multidisiplinary, 2025)
Poverty is one of the main issues that affects the social and economic development of a region, including in the context of development in North Sumatra Province. In general, poverty can be understood as the economic inability experienced by individuals or groups to meet the basic needs for a decent life. The causes of poverty are highly complex and are influenced by various factors, both structural and individual. This study was conducted to identify the key factors that play a role in determining the poverty level in the province. Using a multiple linear regression analysis approach, the study revealed that there are four main factors that influence the poverty level in North Sumatra. Based on the results, four variables were found to influence the poverty rate in North Sumatra Province, namely: GRDP (25.7%), HDI (61.1%), Unemployment Rate (9.1%), and Life Expectancy (13.9%). The multiple linear regression model that affects the poverty rate is as follows: Y=-25,471-0,662X_1-0,621X_2-1,037X_3+1,545X_4.